A marketing scheme for making money off innocent people: A user's manual - Kaushik Basu (Cornell University, Center for Analytical Economics (CAE), 2009)
Firms often give away free goods with the product that they sell. Firms often give stock options to their top management and other employees. Mixing these two practices-giving stock options to consumers who buy the firm's product-, creates a deadly brew. Large numbers of consumers can be lured into buying this product, giving the entrepreneur huge profits and the consumers a growing profit share. But this is a camouflaged Ponzi that will ultimately crash. By analogy it is argued that the common practice of giving stock options to employees can be a factor behind financial crashes.
Keywords: M30; G18; G32; L20; D92; 330; marketing; stock options; financial scams; product bundling; Marketing; Aktienoption